Tun Abdul Razak bin Dato' Hussein dasar luar Malaysia, 1970-1976 - Rozeman Abu Hassan (Penerbit Universiti Pendidikan Sultan Idris, 2003)
Malaysian foreign policy under the leadership of Abdul Razak bin Dato' Hussein, Prime Minister of Malay 1976